2022
DOI: 10.31219/osf.io/drvq9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohort profile: The Corona Behavioural Unit COVID-19 cohort, a longitudinal mixed-methods study on COVID-19-related behaviour, well-being and policy support in the Netherlands

Abstract: In response to the COVID-19 pandemic in the Netherlands, the National Institute of Public Health and the Environment (RIVM) established a longitudinal collaborative cohort study to examine adherence to COVID-19 behaviours, its psychosocial determinants, participant well-being, trust in the Dutch government, with additional attention for COVID-19 test and vaccination uptake. The cohort profile gives a comprehensive description of the cohort’s recruitment and its mixed-method design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The importance of differences in perceived trade-offs in understanding differences in support for mitigation measures is underscored by experimental research (3,14), as well as population surveys of population support showing that support for COVID-19 mitigation is lower and decreases when people more strongly believe that economic, educational, and social costs are insufficiently weighed (5,6). Further evidence for the importance of potential benefits and costs in understanding differences in support for mitigation measures is provided by research that found that more support for and adherence to COVID-19 mitigation measures is associated with a higher perceived need for such measures (20), as indicated by concern about COVID-19 (11), experienced public health danger or personal health threat of COVID-19 (8,10,12), or perceived health risks of COVID-19 to self or important others (5-7). In addition, research reporting associations between support for mitigation measures and trust, including in governments, science, and pharmaceutical companies (4-6), suggests that differences in support between population subgroups may reflect differences in social trust between these groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of differences in perceived trade-offs in understanding differences in support for mitigation measures is underscored by experimental research (3,14), as well as population surveys of population support showing that support for COVID-19 mitigation is lower and decreases when people more strongly believe that economic, educational, and social costs are insufficiently weighed (5,6). Further evidence for the importance of potential benefits and costs in understanding differences in support for mitigation measures is provided by research that found that more support for and adherence to COVID-19 mitigation measures is associated with a higher perceived need for such measures (20), as indicated by concern about COVID-19 (11), experienced public health danger or personal health threat of COVID-19 (8,10,12), or perceived health risks of COVID-19 to self or important others (5-7). In addition, research reporting associations between support for mitigation measures and trust, including in governments, science, and pharmaceutical companies (4-6), suggests that differences in support between population subgroups may reflect differences in social trust between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Pandemic fatigue is noted to have gained prominence as an explanation of a decline in following the rules to prevent the spread of COVID-19 (19). However, its occurrence is contested (19)(20)(21). We found two studies that explicitly aimed to assessed evidence of pandemic fatigue based on trends in adherence to COVID-19 mitigation measures, of which one did not find the continual gradual decrease in adherence (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In April 2020, which corresponded with the first months of the COVID-19 pandemic in the Netherlands, the Corona Behavioral Unit at the National Institute for Public Health and the Environment, the Netherlands, launched a dynamic cohort study to monitor the Dutch population, including the well-being of people over time. 21 We invited the participants of existing panels of the 25 regional Public Health Services in the Netherlands to participate in a survey. To compensate for dropout, for several rounds we recruited additional respondents.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the Corona Behaviour & Well-being cohort study, a dynamic cohort study conducted between April 2020 and September 2022 among the Dutch population by the Behavioural Unit of the National Institute for Public Health and The Environment (RIVM). More information about the cohort study is available in a cohort profile (van den Boom et al, 2022). We selected five rounds that strongly differed with respect to the severity of the Covid-19 situation as well as the vaccination rate, to represent the different stages of the pandemic in the Netherlands.…”
Section: Datamentioning
confidence: 99%